The Art of Poser and Photoshop: The Official e-frontier Guide / Stephen Burns - Burns, Stephen
Expand your digital art possibilities with Poser Pro and Photoshop CS4! If you are a digital artist who has been frustrated with the limitations and confusing interfaces of 3D software products in the past, "The Art of Poser and Photoshop: The Official Guide" will show you how to harness the dynamic capabilities of both Poser and Photoshop to create fascinating and unique imagery. Using Poser Pros intuitive approach and its extensive library of characters, props, and environments you can focus on the creative aspects of 3D modeling. Then, using the sophisticated functionality of Photoshop CS4, you can enhance and perfect your creation, adding texture, animating layers, applying light, and more. Every chapter features full-color tutorials to guide you through the process of using each product to create an imaginative work of art from beginning to end. And all images used in the tutorials are available for download on the books companion website. Get ready to maximize your artistic vision with "The Art of Poser and Photoshop: The Official Guide!"